Integrative Approach in the Management of Janusandhivata w.s.r. to Osteoarthritis - Pushpendra Kumar; Kiran M. Shah; Rakesh R. Tiwari (International Journal of Ayurveda and Pharma Research, 2022)
Janusandhivata is a Vataj disorder in which Vata resides in Janu sandhi (Vimarga gaman) and produces various signs and symptoms according to its Gunas. In modern sciences Janusandhivata is correlated with osteoarthritis. In the present study integrative measures like allopathy medicines, Ayurvedic medicines and Karmas, yoga, naturopathy and exercises are studied for the effective relief of symptoms of Janu sandhigata vata i.e., OA. Integrative measures are studied to provide effective and fast relief to the patient. Modern treatment provides instant relief while on the other hand Ayurveda heals by curing the disease from root and is considered Apunarbhav chikitsa which means it prevents recurrence of the disease. Other measures aid in achieving the ultimate goal of cure from the disease.